AMH and other markers of ovarian function in patients with Turner syndrome – a single center experience of transition from pediatric to gynecological follow up - Hagen, Casper P.; Fischer, Margit Bistrup; Mola, Gylli; Mikkelsen, Theis Bech; Cleemann, Line Hartvig; Gravholt, Claus Højbjerg; Viuff, Mette H.; Juul, Anders; Pedersen, Anette Tønnes; Main, Katharina Maria (Frontiers in Endocrinology, 2023)
Turner syndrome (TS) is a chromosomal disorder that affects about 1 in 2500 female births and is characterized by the partial or complete absence of the second X chromosome. Depending on karyotype, TS is associated with primary ovarian insufficiency (POI). Approximately 50% of girls with a mosaic 45,X/46,XX karyotype may enter puberty spontaneously, but only 5-10% of women with TS achieve pregnancy without egg donation. In this review, we will evaluate the clinical use of markers of ovarian function in TS patients. Based on longitudinal studies of serum concentrations of reproductive hormones as well as ovarian morphology in healthy females and patients with TS, we will evaluate how they can be applied in a clinical setting. This is important when counseling patients and their families about future ovarian function essential for pubertal development and fertility. Furthermore, we will report on 20 years of experience of transition from pediatric to gynecological and adult endocrinological care in our center at Rigshospitalet, Copenhagen, Denmark.